MEASUREMENT OF THE SUCCESS OF STUDENT ACTIVITIES PERFORMANCE SYSTEM (SAPS) WITH DELONE AND MCLEAN MODEL - Septiana, Meuthia; Elfiswandi, Elfiswandi; Zefriyenni, Zefriyenni (Jurnal Apresiasi Ekonomi, 2022)
The purpose of this research is to measure the success of the Student Activities Performance System (SAPS) using the Delone and Mclean model at the Faculty of Medicine, Baiturrahmah University. This model has been implemented and utilized since 2017, but the measurement and the effectiveness of this model have not been measured yet. The research method used in this study was quantitative. The data gained were analyzed using the structural equation model (SEM). This study showed the relationship of the system quality, the information quality, the service quality, user satisfaction, users, and net benefits. The results of this study proved that there are seven accepted hypotheses and five rejected hypotheses for direct influence